Complete chloroplast genome sequences of Debregeasia orientalis (Urticaceae) - Ruo-Nan Wang; Jie Liu; Zhong-Hu Li; Zeng-Yuan Wu (Mitochondrial DNA. Part B. Resources, 2019)
Debregeasia orientalis is an economically and ecologically important species, which belongs to the genus Debregeasia within the family Urticaceae. The complete chloroplast genome size of D. orientalis is 155,894 bp in length, including a large single copy (LSC) region of 85,558 bp, a small single copy (SSC) region of 19,064 bp, and a pair of inverted repeats (IRs) of 25,636 bp. The genome contains 112 genes, including 78 protein-coding genes, 30 tRNA genes, and four rRNA genes. The GC content in chloroplast genome, LSC region, SSC region, and IR region were 36.3%, 34.0%, 29.4%, and 42.7%, respectively. A total of 15 species are used to construct the phylogenetic tree of Rosales, employing the maximum likelihood (ML), and the results showed that D. orientalis is closely related to Debregeasia saeneb.